Algorithmic game theory : 9th International Symposium, SAGT 2016, Liverpool, UK, September 19-21, 2016, proceedings /: 9th International Symposium, SAGT 2016, Liverpool, UK, September 19-21, 2016, proceedings. (2016) - Unknown
No abstract available